Pengaruh kualitas kehidupan kerja (qwl) terhadap produktivitas Kerja Tenaga Kesehatan (NAKES) di UPTD Puskesmas Mekar Baru Tangerang - Ayuni Ayuni (Vanchapo Health Science Journal, 2023)
According to the World Health Organization (WHO), quality of life is a conditionin which an individual is not only free from disease and weakness, but also balancesphysical, mental and social functions. So that the measurement of quality of life canbe seen from four areas of function, namely physical, psychological, social andenvironmental. Indonesia's labor productivity is at 74.4%. This productivity level isbelow the average of the Association of Southeast Asian Nations (ASEAN), whichis 78.2%. Still inferior to neighboring countries such as the Philippines (86.3%),Singapore (82.7%), Thailand (80.1%) and Vietnam (80%), said Secretary Generalof the Ministry of Manpower, Anwar Sanusi, in a written statement. , Jakarta,Friday, November 13 2020 Types and Methods of Research The type of researchused in this study is quantitative using descriptive analysis with a cross sectionalapproach, namely conducting research to find relationships between theindependent variables, namely Quality of Work Life (QWL) and the independentvariable is Work productivity. Spearman's rho Correlation Test is one of thenonparametric analyzes to determine the strength of the relationship between twovariables on an ordinal scale. The results showed that most of the 38 respondentswho had a high QWL were 28 respondents (73.7%). most of those who have highwork productivity are 27 respondents (71.1%). There is no influence between thequality of work life on work productivity at the UPTD Puskesmas Mekar BaruTangerang, as evidenced by the value ℓvalue 0.092 which means greater than(ℓvalue 0.05).